The perioral muscular phenomenon: Part I. - Frederick Sidney (Sciendo, 1991)
More than twenty-five years of studying the perioral musculature, clinical observation of the dental and peridental tissues of hundreds of patients, and examining seven anatomy books - have revealed that there is a serious deficiency in our knowledge of this musculature and its effects on the dental tissues and this part of the face. Believed to be of no unusual significance, it has been almost ignored through the years. One hears vague terms such as lip pressure and cheek pressure; but no comprehensive studies of this musculature, how it functions and the effects of these functions are to be found in literature. By its actions, this musculature effects many phases of dentistry, directly or indirectly; and orthodontics is affected most of all. By its manipulations of the dental tissues, the alveolar bone and gingiva, it ultimately determines the position of the teeth. Almost every person is a live laboratory specimen in which pressure signs or damage to the tissues can be observed. By reading these signs, the strength and physical configuration of the pertinent parts of the musculature can be determined. This ability to 'read the signs' should be actively developed to fine tune the diagnosis. The perioral musculature phenomenon is a significant aetiological factor in many malocclusions.